Transnational Labour Vulnerability and Shared Precarity in the Neoliberal World Order: A Neo-Marxist Study of Mohsin Hamid’s Exit West - Shah, Ayaz Muhammad (Pakistan Languages and Humanities Review, 2025)
This paper aims to critically examine the global condition of working class under neoliberal capitalism as represented in Mohsin Hamid’s Exit West, contending that economic precarity and systemic vulnerability are transnational phenomena impacting workers across both the Global South and Global North. Neoliberalism—an advanced stage of capitalism— dismantles the welfare infrastructures, thereby intensifying labour insecurity and marginalisation. Engaging with contemporary neo-Marxist and leftist theorists such as David Harvey, Werlhof, and Rajesh Makwana, the study interrogates how neoliberal regimes facilitate upward wealth redistribution while undermining collective protections. Through close textual analysis, the novel is shown to destabilise the dominant narrative that migration to the West guarantees economic opportunity, exposing instead the transnational reach of neoliberal disposability. By situating Exit West within the framework of Anglophone Pakistani resistance literature, the research foregrounds the novel’s critical intervention into global labour politics and its call for post-neoliberal solidarities transcending national and economic boundaries.